PTU-021 Variation in diathermy use for colonic polypectomy – results from a national survey. (17th June 2017) - Verma, AM; Chilton, A
Abstract : Introduction: The transition from trainee to consultant and subsequent accredited bowel cancer screening colonoscopist reveals variability in diathermy practice for colonic polypectomy. There is no standardised teaching with a paucity of guidelines. We therefore designed a survey to evaluate current practice. Method: This national survey was hosted on www.surveymonkey.co.uk, it has been approved by the endoscopy committees of the BSG and Association of Coloproctology of Great Britain and Ireland (ACPGBI) and was circulated to their memberships. The questions: 1. Which region do you work in? 2. Endoscopy grade and role 3. Endoscopy lists provided in a typical working month 4. What level of polypectomy do you undertake in a typical working month? 5. What diathermy modes do you use for polypectomy in the LEFT side of colon? 6. What diathermy modes do you use for polypectomy in the RIGHT side of colon? 7. Do you use lower diathermy current settings for right side polypectomy vs left side? 8. Do you feel confident in your knowledge and use of diathermy for polypectomy? Results: The survey was open in 2016. Analysis shows: 250/348 (71.8%) completed the full survey from across the United Kingdom. 159 Gastroenterologists (63.6%), 36 Surgeons (14.4%), 34 Gastroenterology Trainees (13.6%), 21 others (8.4%). Predominant use of coagulation current or coagulation and cutting combination for small and large pedunculated polypectomy. Wide variance in diathermy modes for polypectomy of large sessile and very large polyps. High use of cold snare polypectomy for small sessile polyps (right 43.2% > left 34.4%). Low use of endocut mode irrespective of size/location of polyp (17.2%–32.0%)%). 204/250 (81.6%) use reduced current settings for right colonic polypectomy. 208/250 (83.2%) confident on knowledge and use of diathermy. Conclusion: When designing a survey the challenge is to capture the information required and balance this with a high completion rate. We have achieved this with a large number of complete responses. The guidance for the management of large non-pedunculated colorectal polyps advises that prolonged pure coagulation current be avoided due to risks of delayed bleeding and thermal injury. 1 Many complications are as direct result of thermal injury and polypectomy is the most frequent therapeutic intervention, appropriate training and BSG formal guidance is lacking. This national survey has exposed wide variations in diathermy use for colonic polypectomy, further analysis is ongoing prior to publication of a paper and we will make representations to the BSG and ACPGBI endoscopy committees to provide a platform to develop training and guidance to improve patient safety. Reference: . Rutter MD, et al. The guidance for the management of large non-pedunculated colorectal polyps. Gut2015;64:1847–1873. doi:10.1136/gutjnl-2015-30957 Disclosure of Interest: None Declared